Dissecting the region around IceCube-170922A: the blazar TXS 0506+056 as the first cosmic neutrino source. Issue 1 (12th July 2018) - Padovani, P; Giommi, P; Resconi, E; Glauch, T; Arsioli, B; Sahakyan, N; Huber, M
ABSTRACT: We present the dissection in space, time, and energy of the region around the IceCube-170922A neutrino alert. This study is motivated by: (1) the first association between a neutrino alert and a blazar in a flaring state, TXS 0506+056; (2) the evidence of a neutrino flaring activity during 2014–2015 from the same direction; (3) the lack of an accompanying simultaneous γ-ray enhancement from the same counterpart; (4) the contrasting flaring activity of a neighbouring bright γ-ray source, the blazar PKS 0502+049, during 2014–2015. Our study makes use of multiwavelength archival data accessed through Open Universe tools and includes a new analysis of Fermi -LAT data. We find that PKS 0502+049 contaminates the γ-ray emission region at low energies but TXS 0506+056 dominates the sky above a few GeV. TXS 0506+056, which is a very strong (top percent) radio and γ-ray source, is in a high γ-ray state during the neutrino alert but in a low though hard γ-ray state in coincidence with the neutrino flare. Both states can be reconciled with the energy associated with the neutrino emission and, in particular during the low/hard state, there is evidence that TXS 0506+056 has undergone a hadronic flare with very important implications for blazar modelling. All multimessenger diagnostics reported here support a single coherent picture in which TXS 0506+056, a very high energy γ-ray blazar, is the only counterpart of all the neutrino emissions in the region and therefore the most plausible first non-stellar neutrino and, hence, cosmic ray source.